Examining and Comparison of Education and Training Systems from Pre-School to High School in Turkiye and the Turkish Republic of Northern Cyprus, States of the Turkic World - Akkaya, Burcu; Celik, Sibel Acisli; Ergin, Ismet (Asian Journal of Contemporary Education, 2022)
The aim of the research is to examine the structure of education and training from pre-school to high school in Turkey and the Turkish Republic of Northern Cyprus, the States of the Turkic World, and to compare them with each other. In order to achieve this aim, it has been collected through document review from the literature related to each of these states, printed scientific and official sources, and data on the official websites of the ministries of the relevant states. While analyzing the data, descriptive analysis method was used. In the research, the themes of languages of education, pre-school education, primary school education, secondary school education and high school education were created by considering the descriptive analysis method stages; The sources that can be accessed and evaluated within the scope of the research were examined within the scope of these themes. The data obtained were defined, supported by direct quotations, and interpreted by adhering to the original form of the data. At the end of the research, it was concluded that there are similarities and differences in the structure of the education and training systems of the Turkish States. Based on these results, at the end of the research, suggestions were presented for the continuation and further development of the common points and good practices in the education and training system of the Turkish States with an increasing contribution.